Community Partnership Program: Mangrove Planting in the Coastal Area of Garassikang Village, Jeneponto Regency, South Sulawesi - Abdul Malik; Abdul Rahim; Ronald Ronald; Andi Sitti Asmah; Ulfah Syam; Nur Hamdi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Aquaculture is one of the essential community livelihoods in Garassikang Village, West Bangkala District, Jeneponto Regency. However, abrasion that occurs in the coastal area of this village becomes a threat to the sustainability of community aquaculture ponds. The objectives of this Community Partnership Program (Program Kemitraan Masyarakat/PKM) is to rehabilitate of mangrove area for preventing abrasion on the coast of Garassikang Village, Jeneponto Regency. A total of 1,500 mangrove seeds from Rhizophora sp. have been planted in this program and involve the government village and community as partners. We implemented the planting distance of mangrove seed is 1m x 1m and giving a space for fishermen boat access. More attention of partners to maintain and conserve the mangrove planted become a worthy contribution to halt coastal abrasion and the sustainability of mangrove area and aquaculture activity in the coastal area of this village.